Phosphorus recovery from pig farm biogas slurry by the catalytic ozonation process with MgO as the catalyst and magnesium source. (1st October 2020) - Zeng, Weishen; Wang, Dehan; Luo, Zifeng; Yang, Jie; Wu, Zhaoyun
Abstract: In China, most large-scale pig farms use a large-volume cover lagoon digester to treat swine wastewater and recover energy, but the effluent biogas slurry is dark in color, contains refractory organic matter, high NH3 –N, and low BOD5 /COD (B/C), and exhibits poor biodegradability, and it is difficult for the effluent from the wastewater treatment system to reach the standard discharge requirements. Therefore, it is necessary to study the pretreatment of biogas slurry. The purpose of this study is to use ozone to pretreat the biogas slurry, increase the ozone oxidation efficiency by adding magnesium-containing materials, simultaneously recover phosphorus (struvite) as a magnesium source, and improve the wastewater B/C. In this study, a laboratory ozone generator and ozone reactor combination device were used. The experiment investigated the effects of the magnesium material type, catalyst dosage, ozone dosage and pH on catalytic ozonation and phosphorus recovery efficiency. The results show that MgO is superior to MgCO3, dolomite and MgCl2 as a catalyst. With the addition 1.5 g/L MgO and an ozone dosage of 0.58 g/L, the COD, UV254 and chroma removal rates of biogas slurry reached 55.43%, 70.22% and 88.87%, respectively. At pH 10, the phosphorus recovery rate reached 98.47%. The SEM-EDX and XRD analyses of the phosphorus recovery product revealed that the product contained a certain amount of MAP in addition to MgO. A 3D-EEM analysis of water quality before and after ozonation of biogas slurry showed that humic acids were significantly reduced after ozonation. The GC-MS results showed that catalytic ozonation can effectively degrade refractory organic pollutants, and the biogas slurry B/C increased after pretreatment, which improved biodegradability. After ozonation pretreatment of biogas slurry, the water quality of effluent treated by a sequencing batch reactor (SBR) reached the standard discharge requirements. Using ozone to pretreat pig farm biogas slurry and adding MgO as a catalyst can not only improve ozone oxidation efficiency but also achieve phosphorus recovery. The results provide an innovative technology for the pretreatment of biogas slurry in pig farms. Graphical abstract: Image 1 Highlights: MgO catalytic ozonation pretreatment of biogas slurry is superior to single O3 . MgO can also be used as a Mg source to recover P (MAP) during catalytic ozonation. The parameters of MgO catalytic ozonation and the P recovery process were optimized. The P recovery rate reached 98.47% at pH 10.